The Influence of BI Rate, Inflation, and Exchange Rate on The IDX Composite Stock Index (IHSG) - Ratnaningrum, Ratnaningrum; Putri, Bella Kharisma; Wulandari, Retno; Purnama, Kusna Djati (International Journal of Science, Technology & Management, 2023)
This study investigates the impact of variations in the BI rate, inflation rate, and the USD/IDR (US Dollar to Indonesian Rupiah) exchange rate on the IDX Composite Index (IHSG). The Composite Stock Price Index is one of the resources that investors use to choose their investing strategy. Inflation, exchange rates, business interest rates, and the IHSG are among the variables that make up the sample used in this study, which spans 60 months from January 2015 to December 2019. The analysis of the data was done using multiple regression methods. According to the findings, the IHSG is negatively impacted by changes in the BI rate, positively impacted by changes in the USD/IDR exchange rate, and not impacted at all by changes in the inflation rate. Additional analysis should look at additional potential macroeconomic factors.